Enforcing Religious Moderation Among Generation Z Muslims in the Digital Era Through Critical - Faradhillah, Nadia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This qualitative study explores the potential of critical reading as a tool for promoting religious moderation among Generation Z Muslims. The research focuses on a group of young Muslims aged 18-21 years enrolled in a Religious Moderation course at a State Institute of Islamic Studies in Indonesia. The study investigates how training in critical reading of religious texts can influence their interpretations of Islamic teachings and their attitudes towards diversity and pluralism. Data was collected through in-depth interviews, focus group discussions, and participant observation. The findings suggest that fostering critical reading skills can encourage more moderate and inclusive understandings of Islam among Generation Z Muslims, potentially mitigating the influence of religious extremism. This research contributes valuable insights into the role of education in promoting religious tolerance and countering radicalization among young Muslims in the digital age.